Long Volar Plating for Metadiaphyseal Fractures of Distal Radius: Study Comparing Minimally Invasive Plate Osteosynthesis versus Conventional Approach - Pire, Emilie; Hidalgo Diaz, Juan José; Salazar Botero, Santiago; Facca, Sybille; Liverneaux, Philippe A. (Journal of Wrist Surgery, 2017)
Background Minimally invasive plate osteosynthesis (MIPO) has been used in wrist surgery for several years. The purpose of this retrospective study was to compare clinical and radiologic outcomes of MIPO technique with those of a conventional approach in the treatment of metadiaphyseal distal radius fracture by long volar plating.Materials and Methods Our series consisted of 32 fractures in 31 patients, mean age 63.9 years, including 16 men and 15 women. MIPO technique was used in 15 wrists (group 1) and conventional approach (> 60 mm of skin incision) in 17 wrists (group 2). In group 1, a long volar plate was inserted under pronator quadratus through a 15- to 30-mm distal incision then fixed to the epiphysis of the distal radius. Then, through a 15- to 30-mm proximal incision, the plate was fixed to the diaphysis of the radius, thus reducing the fracture.Results In group 1, mean distal incision size was 23.5 and 16.9 mm for proximal one. Mean total scar size (sum of both distal and proximal incisions) was 40.0 mm in group 1 and 84.1 mm in group 2. Mean tourniquet time was 58.4 minutes in group 1 and 68.9 minutes in group 2. At latest follow-up, no significant difference was noted in both the groups concerning pain, quick-DASH score, grip strength, ROM, and radiologic data. One extensor pollicis longus rupture treated by tendon transfer was done in group 1.Conclusion The MIPO technique for metadiaphyseal fractures of the distal radius by long volar plating has cosmetic and economic advantages compared with the conventional approach. Conversion to conventional approach is possible at any time in case of technical difficulties.Level of Evidence III.
Keywords: fractures; minimally invasive plate osteosynthesis; distal radius; mini-invasive; long plate; metadiaphyseal fracture